IDNLearn.com provides a platform for sharing and gaining valuable knowledge. Discover comprehensive answers from knowledgeable members of our community, covering a wide range of topics to meet all your informational needs.

Check whether the value given in brackets is a solution to the given equation or not:

(i) [tex]x + 5 = 3 \, \text{(}x = 2\text{)}[/tex]

(ii) [tex]8n + 5 = 21 \, \text{(}n = 2\text{)}[/tex]

(iii) [tex]4x + 3 = 5 \, \text{(}x = -2\text{)}[/tex]

(iv) [tex]5p + 3 = 7 \, \text{(}p = -3\text{)}[/tex]

(v) [tex]4p - 3 = 13 \, \text{(}p = 1\text{)}[/tex]

(vi) [tex]-3p - 2 = 10 \, \text{(}p = -4\text{)}[/tex]


Sagot :

Certainly! Let's solve each part one by one to check whether the given values are solutions to the respective equations.

### Part (i)
Equation: \( x + 5 = 3 \)
Given \( x = 2 \).

Substitute \( x = 2 \) into the equation:
[tex]\[ 2 + 5 = 7 \][/tex]
The right-hand side of the equation is 3, but the left-hand side, after substitution, gives 7.

Since \( 7 \neq 3 \), \( x = 2 \) is not a solution to \( x + 5 = 3 \).

### Part (ii)
Equation: \( 8n + 5 = 21 \)
Given \( n = 2 \).

Substitute \( n = 2 \) into the equation:
[tex]\[ 8(2) + 5 = 16 + 5 = 21 \][/tex]
Both sides of the equation are equal to 21.

Since \( 21 = 21 \), \( n = 2 \) is a solution to \( 8n + 5 = 21 \).

### Part (iii)
Equation: \( 4x + 3 = 5 \)
Given \( x = -2 \).

Substitute \( x = -2 \) into the equation:
[tex]\[ 4(-2) + 3 = -8 + 3 = -5 \][/tex]
The right-hand side of the equation is 5, but the left-hand side, after substitution, gives -5.

Since \( -5 \neq 5 \), \( x = -2 \) is not a solution to \( 4x + 3 = 5 \).

### Part (iv)
Equation: \( 5p + 3 = 7 \)
Given \( p = -3 \).

Substitute \( p = -3 \) into the equation:
[tex]\[ 5(-3) + 3 = -15 + 3 = -12 \][/tex]
The right-hand side of the equation is 7, but the left-hand side, after substitution, gives -12.

Since \( -12 \neq 7 \), \( p = -3 \) is not a solution to \( 5p + 3 = 7 \).

### Part (v)
Equation: \( 4p - 3 = 13 \)
Given \( p = 1 \).

Substitute \( p = 1 \) into the equation:
[tex]\[ 4(1) - 3 = 4 - 3 = 1 \][/tex]
The right-hand side of the equation is 13, but the left-hand side, after substitution, gives 1.

Since \( 1 \neq 13 \), \( p = 1 \) is not a solution to \( 4p - 3 = 13 \).

### Part (vi)
Equation: \( -3p - 2 = 10 \)
Given \( p = -4 \).

Substitute \( p = -4 \) into the equation:
[tex]\[ -3(-4) - 2 = 12 - 2 = 10 \][/tex]
Both sides of the equation are equal to 10.

Since \( 10 = 10 \), \( p = -4 \) is a solution to \( -3p - 2 = 10 \).

### Summary
To summarize, the given values are solutions to the equations as follows:
(i) \( x = 2 \): Not a solution
(ii) \( n = 2 \): Solution
(iii) \( x = -2 \): Not a solution
(iv) \( p = -3 \): Not a solution
(v) \( p = 1 \): Not a solution
(vi) [tex]\( p = -4 \)[/tex]: Solution
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Your search for answers ends at IDNLearn.com. Thank you for visiting, and we hope to assist you again soon.